The influence of TCM constitutions and neurocognitive function in elderly Macau individuals - Zhuo Zhang; Yaochen Chuang; Xinyu Ke; Ji Wang; Youhua Xu; Yonghua Zhao; Ying Bian (BMC, 2021)
Abstract Background Traditional Chinese medicine (TCM) constitution contributes to predicating disease occurrence and pathological progress. In this study, we investigate the correlation between TCM constitution and neurocognitive function in elderly Macau individuals. Methods A total of 313 older adults from elderly healthcare centers were recruited at random. The data of gender, age, education, sleeping hours, physical activities were collected, and the Geriatric Depression Scale, Hong Kong version of the Montreal Cognitive Assessment (MoCA) and categories of TCM constitution were administered. Results Of the 313 elderly individuals enrolled in this study, 86 (27.48%) were of balanced constitution. Among the other categories of TCM constitution, the most was Yin-deficiency (23.32%), followed by 53 (16.93%) with Phlegm-dampness. The average neurocognitive score of all elderly individuals was 18.01 ± 6.25. After adjusting for all possible confounds, multiple linear regression analysis showed that Qi-depressed constitution and neurocognitive scores were negatively correlated (β = − 2.66, 95%CI − 4.99 ~ − 0.33), Meanwhile, Yin-deficient constitution and neurocognitive scores were negatively correlated (β = − 2.10, 95%CI − 3.73 ~ − 0.47). Compared with balanced constitution, Qi-depressed constitution mainly affected visual-spatial ability dimension (β = − 0.91, 95%CI − 1.54 ~ − 0.28) and naming dimension (β = − 0.64, 95%CI − 1.04 ~ − 0.25), Yin-deficient constitution mainly affected visual space dimension (β = − 0.53, 95%CI − 0.97 ~ − 0.08). Conclusion Qi-depressed and Yin-deficient constitutions are associated with and contributed to the decline of neurocognitive function in senior adults, especially visual-spatial ability and naming dimensions. Further investigations into how TCM constitutions interact with neurocognitive function are needed.